TRADITIONAL HEALERS AND NURSES: A QUALITATIVE STUDY ON THEIR ROLE ON SEXUALLY TRANSMITTED INFECTIONS INCLUDING HIV AND AIDS IN KWAZULU-NATAL, SOUTH AFRICA - Mngqundaniso, Nolwandle; Peltzer, Karl (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
The aim of this study was to investigate the role of traditional healers in sexually transmitted infections including HIV/AIDS and collaboration between the traditional and biomedical health care systems as seen by nurses and traditional healers. A convenient sample of 15 professional nurses and 15 traditional healers were interviewed using a semi-structured questionnaire. Qualitative analyses identified the following themes: (1) attitude and respect, (2) collaboration between traditional healers and nurses, (3) control/regulation of (traditional) health practices, (4) training needs of healers and nurses. The main results indicated that the professional nurses had mixed attitudes towards traditional healers, mostly negative (e.g. lacked training, used expired medicines, gave improper dosages, and kept poor or no records), but, also positive, such as contributing to the management of opportunistic infections (STIs). The traditional healers also had mixed attitudes towards nurses. The traditional healers believed that nurses undermined their work (did not accept their efficacy in treatment and consequently did not refer patients). Notably, most of the traditional healers were willing to learn and refer patients to clinics and hospitals, while this was not true for the nurses.